PENERAPAN METODE RESITASI UNTUK MENINGKATKAN KEMAMPUAN HAFALAN SURAT-SURAT PENDEK PESERTA DIDIK KELAS II MI BANGSAL PADA MATA PELAJARAN AL QUR’AN HADITS - Guntina, Hana; Darisman, Dede; Masturoh, Imas (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2017)
This study aims to examine and analyze the application of recitation methods to improve the memorization ability of short letters to class II MI Bangsal students in the Hadith Qur'an subject. The results of the above conclusions are as follows: 1) The memorization ability of students in the Al-Quran Subject The hadith subject matter memorization of short letters using the recitation method in class II MI Bangsal Darmaraja Village District of Lumbung has increased, this is evidenced by the results obtained assessment of the memorization ability of students in the implementation of learning in the first cycle reached 84.62% with an average value of 76 and the second cycle reached 100% with an average value of 86.03; 2) The learning of Al-Quran Subjects Hadith subject matter memorization of short letters using the recitation method in class II MI Darmaraja Village Ward Lumbung District experienced an increase, as evidenced by the assessment of the implementation of learning in the first cycle reached 84.62% with the average value is 76 and the second cycle reaches 100% with an average value of 86.03. 3) The results of Al-Quran learning in the subject matter of memorizing short letters using the recitation method in class II MI Bangsal has increased, as evidenced by the learning outcomes of students in cycle I reached 84.62%, and cycle II reached 100% (increase 15.38%).